Pengaruh Lama Pengasinan terhadap Organoleptik Telur Itik: organoleptic - REFIKA KOMALA; Rahmat Hidayat; Rini Elisia (Jurnal Peternakan Mahaputra, 2022)
Duck eggs are poultry products that invite higher nutrients value than chicken eggs, especially the content of proteins, fats and carbohydrates. The existence of eggs as a source of animal protein is actually very much needed by the community, but the high level of protein and fat possessed by duck eggs makes the aroma of duck eggs somewhat different from chicken eggs, making some people dislike it as a source of family side dishes. The purpose of this study was to determine the effect of salting duration on the egg organolpetic. The purpose of this study was to determine the effect of long salting on the organoleptic of duck eggs. The study was conducted by expletives in which the hail obtained, modulated and transformed which was then processed using a Complete Randomized Design (RAL) according to Steel and Torrie (1993). The results showed that the effect of salting duration did not differ markedly (P<0.05%) to the aroma, color, texture and taste of egg white and yolk. Conclude that the length of salting has no effect on the aroma, color, texture, taste of egg white and taste of egg yolk.